Second‐line chemotherapy for non‐small cell lung cancer - Bonfill Cosp, Xavier (Cochrane Database Syst Rev, 2002)
BACKGROUND: The role of second‐line chemotherapy for the treatment of patients with non‐small cell lung cancer (NSCLC) who have relapsed or failed to respond to first‐line treatment was unclear. OBJECTIVES: To determine the effectiveness of any second‐line chemotherapy in patients with NSCLC. SEARCH METHODS: Medline (1966‐July 2001), Embase (1974‐July 2001), Cancerlit (1993‐July) and tthe Cochrane Central Register of Controlled Trials (CENTRAL, issue 2 2001) were searched. In addition a handsearch was performed and experts in the field contacted to identify any further studies that had not been found by the electronic searches. SELECTION CRITERIA: Randomised controlled clinical trials in which any second‐line chemotherapy was compared with placebo or best supportive care in patients with NSCLC who had failed to respond to any previous chemotherapy regimen. DATA COLLECTION AND ANALYSIS: Data were extracted by 2 independent authors and revised by a third author. MAIN RESULTS: Only one study was included. This study included a total of 204 patients who were randomised to receive either doxetaxel or best supportive care. Following an unacceptably high toxic death rate the dose of doxetaxel was reduced from 100 mg/m² to 75 mg/m². Docetaxel gave an extra 2.4 months survival ‐ an average of 7.0 months vs 4.6 months on best supportive care. At 1 year after diagnosis 29% of doxetaxel treated patients were alive compared with 19% of the best supportive care group. AUTHORS' CONCLUSIONS: Definitive recommendations cannot be made since evidence is only available from one randomised controlled trial which, though of reasonable quality had a number of limitations. There is currently no evidence to support second‐line treatment of patients with poor performance status. Larger, well‐designed controlled trials are needed to further evaluate whether the benefits of second‐line chemotherapy to patients with non‐small cell lung cancer outweigh its risks and costs.